Arthrogenic Muscle Inhibition Following Knee Injury or Surgery: Pathophysiology, Classification, and Treatment - Bertrand Sonnery-Cottet MD; Graeme P. Hopper MD, FRCS (Tr & Orth); Lampros Gousopoulos MD; Thais Dutra Vieira MD; Mathieu Thaunat MD; Jean-Marie Fayard MD; Benjamin Freychet MD; Hervé Ouanezar MD; Etienne Cavaignac MD; Adnan Saithna MD (SAGE Publishing, 2022)
Background: Arthrogenic muscle inhibition (AMI), a process in which quadriceps activation failure is caused by neural inhibition, is common following knee injury or surgery. No classifications exist to describe the variable presentations of AMI following knee injury. Indications: AMI can result in significant morbidity following knee injury, and it is essential to recognize and treat. It is crucial to identify patients at higher risk of postoperative complications as surgery should be delayed for specific rehabilitation programs. Understanding the pathophysiology of AMI is vital as this can guide therapeutic interventions. Technique Description: AMI following knee injury can present in a variety of ways including inhibition of the vastus medialis obliquus (VMO) muscle, extension deficits due to hamstring contracture, as well as chronic extension deficits. They also respond differently to conventional treatment modalities and often require longer and specific rehabilitation programs. Therefore, we propose a classification to define these different presentations. Results: Grade 0 is a normal VMO contraction. Grade 1a is when VMO contraction is inhibited but activation failure is reversible with simple exercises while Grade 1b requires longer and specific rehabilitation programs. Grade 2a is when VMO contraction is inhibited with an associated extension deficit due to hamstring contracture, but activation failure and loss of range of motion is reversible with simple exercises. However, Grade 2b is refractory to simple exercises, and longer and specific rehabilitation programs are required. Grade 3 is a chronic extension deficit that is irreducible without extensive posterior arthrolysis. Conclusion: In conclusion, AMI is a process in which quadriceps activation failure is caused by neural inhibition and is common following knee injury or surgery. Not taking AMI into account preoperatively can result in a very high risk of stiffness postoperatively. We propose a classification for AMI following knee injury or surgery, which describes different presentations and can be used to guide management.